Case Report: When cystic fibrosis, elexacaftor/tezacaftor/ivacaftor therapy, and alpha1 antitrypsin deficiency get together - Kinuani, Rachel; Ezri, Jessica; Kernen, Yann; Rochat, Isabelle; Blanchon, Sylvain (Frontiers in Pediatrics, 2024)
In the last 10 years, the care of patients with cystic fibrosis (CF) has been revolutionized with the introduction of cystic fibrosis transmembrane conductance regulator (CFTR) modulator drugs, with a major impact on symptoms and life expectancy, especially considering the newest and highly effective elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) therapy. Conversely, adverse effects are relatively frequent, with some being life-threatening, such as severe hepatitis. Clinical trials on children starting CFTR modulators have reported transaminase elevations >3× upper limit of the norm in 10%–20% of patients, whereas real-life studies have reported discontinuation rates three times higher than those observed in phase 3 trials. We report the case of a 10-year-old boy with CF who developed severe acute hepatitis 2 weeks after starting ELX/TEZ/IVA therapy. An extensive screening for potential causes led to the identification of heterozygous alpha1-antitrypsin (AAT) deficiency with genotype MZ. The Z allele of SERPINA1 gene, encoding AAT, is known as a risk factor for CF liver disease. We hypothesized that it may act as a risk factor for drug-induced liver injury from CFTR modulators, notably ELX/TEZ/IVA. Therefore, checking AAT before starting CFTR modulator therapy can be suggested, in particular for children with previous, even transient, liver disease.